International Trade, Interprovincial Trade, and Canadian Provincial Growth - Coulombe, Serge (Université d'Ottawa | University of Ottawa, 2002)
This paper provides an empirical analysis of the comparative evolution of interprovincial and international trade and their effects on regional growth for the Canadian provinces since 1981. Two sets of results emerge from the analysis. First, it appears that the rapid expansion of international trade following the Canada-United States Free Trade Agreement with a certain lag did not produce a decrease in interprovincial trade. To the contrary, we found a positive relation between the two trade channels, especially since 1991. Second, using a conditional convergence econometric framework, we found that increased international trade openness has a positive and significant long-run effect on regional standards of living, productivity, and employment. Increased interprovincial trade has a positive effect on GDP per capita and employment; however, the effect appears to be close to zero on labour productivity. / Commerce international, commerce interprovincial et croissance économique régionale au Canada - Dans cette étude empirique, l’auteur analyse l’évolution comparée du commerce international et du commerce interprovincial des provinces canadiennes depuis 1981. Une attention particulière est accordée à l’analyse de l’incidence de l’évolution des liens commerciaux sur la croissance économique des économies provinciales. Deux ensembles de résultats ressortent de l’analyse. En premier lieu, il apparaît que la forte expansion du commerce international qui a suivi avec un certain délai l’Accord de libre-échange canado-américain n’aurait pas entraîné une diminution du commerce interprovincial. Au contraire, l’analyse montre que, surtout depuis 1991, l’expansion du commerce Nord-Sud aurait exercé une incidence positive sur le commerce Est-Ouest. En second lieu, dans le cadre d’une régression de croissance fondée sur un modèle de convergence conditionnelle, l’expansion du commerce international aurait eu un effet de long terme significatif sur le niveau de vie, la productivité et l’emploi des économies provinciales. L’accroissement du commerce interprovincial, pour sa part, n’aurait un effet positif et significatif que sur l’emploi et le PIB par habitant. L’effet du commerce Est-Ouest sur la productivité de la main-d’oeuvre serait nul.
Keywords: Canada and globalization; regional economic integration; conditional convergence; FTA; Canadian provincial disparities